INTUBATING CONDITIONS AND HEMODYNAMIC FLUCTUATIONS WHILE ADMINISTRATING SUXAMETHONIUM AND ATRACURIUM IN PEDIATRIC PATIENTS: A CROSS-SECTIONAL STUDY - Surathul Samrin1, Sneha1, Karanraaj, Sambathkumar, Keerthana, Abishkauf Jenish Beautlin (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Background: This study compares intubating conditions and hemodynamic fluctuations between Suxamethonium and Atracurium in pediatric patients undergoing elective surgeries. A total of patients was divided into two groups: Category S (Suxamethonium) and Category A (Atracurium). Intubating conditions were assessed and graded as excellent, good, moderate, or poor. Methods: Patients were evaluated based on three parameters- jaw relaxation, response to intubation, and vocal cord movement. Results: Category A demonstrated significantly better intubating conditions, with 96.5% rated excellent compared to 75.4% in Category S (p<0.0001). The duration of action was significantly longer with Atracurium (26.6 min) than Suxamethonium (6.8 min). Hemodynamic monitoring showed that Suxamethonium caused greater fluctuations in heart rate and mean arterial pressure post-induction. Significant differences were observed at multiple time points, particularly in heart rate (p<0.0001) and MAP at 5 minutes (p<0.0001). Conclusion: Atracurium provided more stable hemodynamics and superior intubating conditions. The findings suggest Atracurium may be a safer and more effective alternative to Suxamethonium in pediatric intubation.